Indigenous Modernization In New Design and Architectural Renovation Of Rural Housing In The Red River Delta (North Of Vietnam) - NGUYEN, Viet Huy; VU, Thi Huong Lan; TRAN, Van Hai (MAJ - Malaysia Architectural Journal, 2025)
In the minds of the Vietnamese people, the house has always been regarded more than just shelter that keeps them from the heat and rain. It also represents the beauty of the family, traditional culture, and the nurturing of the Vietnamese people’s souls. Vietnam’s rural house design is shaped and evolved in tandem with the country’s natural conditions, including its geographic location and climate, as well as social aspects, including daily life, labor, movement, belief and culture. The architectural style of a rural house is now recognized as both tangible and intangible cultural heritage. Nonetheless, the rural architecture in region has been negatively affected by the uncontrollable development. The integration movement is reshaping rural housing architecture, with major influences from the current urbanization and industrialization. Under the so-called rapid urbanization, the construction of rural houses in Vietnam faces numerous challenges, such as changing production methods, habits and lifestyles, design, economic and technical factors. Traditional architecture is gradually being replaced by high-rise reinforced concrete houses and apartment buildings. The qualities of this countryside housing architecture that were formerly thought to be historic have been endangered. By investigating a number of case studies ranging from theoretical housing designs that have been recognized as world heritage sites to the actual modern rural housing projects that have recently been constructed, the authors can validate research hypotheses, viewpoints, and put forward principles for new rural architecture, which will enhance living quality in Vietnam’s rural areas while still preserving the distinctive features in those traditional villages. It will also be necessary to assess the present rural architecture and offer guidance on modernizing it so that planners and experts are able to make appropriate policies and suggestions, as well as to propose principles for rural architecture in the future, thereby supporting the integration process of rural innovation.